2020
DOI: 10.21203/rs.2.21800/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and Epidemiology of Acute Kidney Injury in a Pediatric Malawian Trauma Cohort: a Prospective Observational Study

Abstract: Introduction Acute kidney injury (AKI) is highly associated with mortality risk in children worldwide. Trauma can lead to AKI and is a leading cause of pediatric death in Africa. However, there is no information regarding the epidemiology of pediatric, trauma-associated AKI in Africa. Methods Prospective cohort study of pediatric trauma patients admitted to a tertiary referral hospital in Malawi. Participants enrolled at admission were followed prospectively throughout their hospitalization. AKI was defined by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We previously showed that the baseline creatinine definition for children has a strong impact on detected AKI incidence and that for this African setting, the new Schwartz equation may be optimal. 13 We conducted a prospective study because retrospective and case-control studies are difficult in low-resource areas in which creatinine values are not routinely obtained. However, only 36 participants developed AKI, and only 12 developed severe AKI (stage 2 or 3), thereby limiting our inferences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that the baseline creatinine definition for children has a strong impact on detected AKI incidence and that for this African setting, the new Schwartz equation may be optimal. 13 We conducted a prospective study because retrospective and case-control studies are difficult in low-resource areas in which creatinine values are not routinely obtained. However, only 36 participants developed AKI, and only 12 developed severe AKI (stage 2 or 3), thereby limiting our inferences.…”
Section: Discussionmentioning
confidence: 99%
“…This validation study of diagnostic accuracy was nested within a prospective cohort study to evaluate the incidence of AKI among admitted trauma patients. 13 The study was conducted at Kamuzu Central Hospital (KCH) in Lilongwe, Malawi.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of AKI increased both in hospital and community settings. It is estimated that the incidence of AKI could be from 2 to 3 cases per 1000 population [2]. It was reported that around 7% of hospitalized patients and about 66% of patients in intensive care units could develop AKI.…”
Section: Introductionmentioning
confidence: 99%